Maneobra a campaign on motorcycles and other transportation options to reduce private car use and alleviate parking problems at the University of the Philippines Diliman - Balanlay, Jerome; Dans, Sandra Michelle (Quezon City College of Fine Arts, University of the Philippines Diliman, 2024)
Parking is one of the primary challenges that private vehicle users face every day. In UP Diliman, parking has become an increasingly significant issue due to the growing number of students who rely on private cars. The influx of private vehicles within the campus leads to on-street parking and contributes to traffic congestion during peak hours.

The main objective of this study is to alleviate parking issues in UP Diliman by reducing students' dependence on private cars. Various alternative transportation options are available on campus, including walking, cycling, public transportation (IKOT Jeeps), motorcycles, and ride-sharing.

This study proposes an intervention to address campus parking problems by promoting the benefits and advantages of alternative transportation among students, titled 'Maneobra.' The researcher designed a series of key visuals strategically placed throughout campus areas, complemented by installations, events, and a social media presence to effectively convey the campaign's message. Maneobra's prototype received positive feedback during testing, and participants expressed willingness to adopt alternative modes of transportation if made available.
Thesis (Bachelor of Fine Arts in Visual Communication) -- University of the Philippines Diliman
Bibliography: leaves 61-63
Keywords: Transportations; Campus parking; Parking facilities